Pengaruh Faktor Keluarga dan Teman Sebaya terhadap Motivasi Generasi Muda Bekerja di Sektor Pertanian - Putra Irwandi; Ninda Novita (Ma'soem University, 2026)
The negative perception among young people regarding work in the agricultural sector is high. Agriculture is viewed as dirty, offering no promise of prosperity, and is predominantly associated with low motivation. This study aims to analyze how family and peer factors influence young people’s motivation to work in the agricultural sector. The approach used in this study is a quantitative descriptive analysis of 169 respondents university studentsselected via purposive sampling through the distribution of an online questionnaire (Google Form). The research variables family support (X1) and peer support (X2) were measured using a 1–5 Likert scale, while motivation (Y) was coded as a dummy variable (1 = high and 0 = low). Data analysis employed binary logistic regression using Microsoft Excel and SPSS version 25. The results indicate that the family support variable has a positive and significant influence on the motivation of the younger generation to work in the agricultural sector. Meanwhile, the peer support variable does not have a significant influence on motivation to work in the agricultural sector. It is hoped that internal environments such as families and external parties, including the government, the community, and peers, can enhance the motivation of the younger generation in the agricultural sector through various programs and guidance relevant to the progress of the times in the future.